Rancang Bangun Sistem Informasi Customer Relationship Management (CRM) Berbasis Web - tukino tukino (Computer Based Information System Journal, 2018)
This can make irresponsible parties libel the company because everyone or customers who join it can read and comment freely on what the customer complained about. Therefore, PT Indoritel Makmur International Tbk (Indomaret) Batam is advised to have an application that can arrange and provide services to complaints or criticism and customer suggestions. To overcome these problems then designed a web-based Customer Relationship Management (CRM) information system. This design aims to facilitate customers in delivering criticism and suggestions or complaints to the service company. This design uses UML modeling diagram (Unifed Modeling Language) such as, Use Case Diagram, Activity Diagram, Class Diagram and Sequence Diagram. In addition, the technologies used in this design system such as Dreamweaver, PHP, and MySQL. The end result of this design is a Web-based Customer Relationship Management (CRM) information system that can be used to manage customer complaints submitted to PT Indoritel Makmur International Tbk (Indomaret) Batam. The Extreme Programming method is the most widely used approach to software development.